Criminology of Sexual Acts Committed by Children - Saimima, Berrygibs Jacob; Hehanussa, Deassy Jacomina Anthoneta; Sopacua, Margie Gladies (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: Child as an unlawful act committed solely as a reaction to pressure or pressure from within and from the child's environment.Purposes of the Research: The aim of this research is to examine and analyze the factors that cause children to commit crimes of sexual intercourse and to analyze and explain efforts to overcome criminal acts of sexual intercourse committed by children.Methods of the Research: The type research to be used is normative legal research, which is a study that examines positive legal provisions, legal principles, legal principles and legal doctrines to answer the legal issues faced.Results Main Findings of the Research: The results of this research show that children have sexual intercourse with children specifically, namely the child is in his teens and his psychological condition is still very unstable, resulting in the child not being able to think long and hard about the criminal act he committed. Efforts to overcome the crime of sexual intercourse committed against children are through preventive measures in a non-penal way, namely by educating the community and schools to monitor and pay attention to a person's activities or behavior so that they do not deviate. So when handling cases against children there needs to be maximum sanctions and punishments aimed at strong self-control so that they are not easily tempted to do something that is not good in their hearts and minds.